Negotiating and Resolving Conflicts in Indonesia through First-Track Diplomacy in Anticipation of Indonesia's Golden 2045 Amidst the Russia Vs Ukraine Conflict - Kaunang, Elfira Sylviani; Gibran, Muhamad Noor (Formosa Journal of Applied Sciences, 2024)
The Russia vs Ukraine conflict has had an impact on global geopolitical stability, such as food, energy, humanitarian, economic, and security crises. The resolution of the conflict requires a strong diplomatic approach to neutralize tensions among Western nations and promote global peace. The objective of this research is to analyze the phases of the conflict, conflict resolution, and Indonesia's diplomatic resilience in resolving the Russia vs Ukraine conflict through first-track diplomacy. The method used in this research is qualitative descriptive, employing data condensation, data display, and conclusion drawing and verification techniques. The research findings show that (1) the current phase of the conflict between Russia and Ukraine is at the ceasefire stage which is characterized by the cessation of hostilities while negotiations and dialogue are ongoing, (2) the conflict resolution required by Russia and Ukraine includes cultural and structural peace building.